Antibiotic Resistance: Treatment and Drug Development Challenges Addressed - Mosley, Mary (MD Conference Express, 2014)
The resistance of infectious organisms to currently available antibiotics is a major medical challenge. The prevalence and mechanisms of multidrug-resistant pathogens vary widely worldwide. In the United States and Europe, the prevalence of methicillin-resistant Staphylococcus aureus (MRSA) appears to have stabilized, while it is increasing in other regions [Dantes R et al. JAMA Intern Med 2013]. Antibiotic resistance to gram-negative bacteria continues to increase and represents one of the biggest challenges.